QR Code-Assisted Pop-Up Book Learning Media for Grade II Elementary School - Prashanti, Ni Nyoman Sathya Prema; Margunayasa, I Gede (MIMBAR PGSD Undiksha, 2022)
Lack of media development used in the learning process in the classroom. This research aims to create a pop-up media book on theme 8 sub-theme 4 assisted by QR code for grade II elementary school. This study used the ADDIE model, but the research carried out only reached the development stage due to time and situation constraints. The trial subjects of this research consisted of two media experts, four material experts, and two practitioners. The data collection method in this research is a questionnaire method by providing an assessment sheet. This study was analyzed using the average formula. The results showed that the validity of the pop-up book media obtained from the average calculation was 4.99, with qualifications suitable for use in the learning process. The average practicality of the media that has been developed is 4.73 with practical qualifications and is very suitable for use in the learning process in grade II elementary school. So, the media developed as a pop-up book assisted by a Qr code learning theme 8 sub-theme 4 is valid and practical to use in the learning process for grade II elementary schools. The implications of this media can be used by the teacher in the learning process so that students feel more comfortable and easier to understand the material in the book and the material explained by the teacher in class.